2015
DOI: 10.1210/jc.2015-2604
|View full text |Cite
|
Sign up to set email alerts
|

A Case for Conservative Management: Characterizing the Natural History of Radiographically Diagnosed Rathke Cleft Cysts

Abstract: The increasingly prevalent use of brain imaging modalities such as MRI has resulted in an increase in the incidental discovery of pituitary lesions. Our study demonstrates that the majority of radiologically diagnosed RCCs remain unchanged or decrease in size over time. These results suggest that, in the absence of pressure symptoms, it is reasonable to manage patients with RCCs conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 12 publications
2
25
1
1
Order By: Relevance
“…Of note, GHD was defined in this study by basal GH levels, which are not recommended for diagnosis. Similar to other reports, we found that the most frequently reported hormone abnormalities were hypogonadism and hyperprolactinemia . Interestingly, while cyst size and extension were similar to those in other studies (Aho et al 62%, Raper 75%, Shin 100%), we detected a higher prevalence of pituitary deficits.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Of note, GHD was defined in this study by basal GH levels, which are not recommended for diagnosis. Similar to other reports, we found that the most frequently reported hormone abnormalities were hypogonadism and hyperprolactinemia . Interestingly, while cyst size and extension were similar to those in other studies (Aho et al 62%, Raper 75%, Shin 100%), we detected a higher prevalence of pituitary deficits.…”
Section: Discussionsupporting
confidence: 91%
“…We can confirm prior findings that a conservative approach is safe in most patients with RCC less than 10 mm in diameter. Our study is the first to demonstrate that, in RCC patients who did not undergo surgery, pituitary function remained stable, with some patients even improving, during follow‐up . Impressively, hyperprolactinemia resolved in 50% of patients during follow‐up.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Yet, based on the current literature, this approach is not necessarily unjustified since it is unclear whether pituitary microadenomas can cause pituitary deficiency, e.g., through a mass effect on adjacent normal tissue. Pediatric endocrinologists should review any questionable images with the radiologist including asking if the lesions are consistent with a pars intermedia/Rathke cleft cyst, a common lesion that rarely grows in size or causes symptoms [18, 19]. …”
Section: Discussionmentioning
confidence: 99%